New insights into the anti-obesity activity of xanthones from Garcinia mangostana. Issue 2 (18th December 2014) - Liu, Qian-Yu; Wang, Yi-Tao; Lin, Li-Gen
Abstract : This article reviews the anti-adipogenic, anti-inflammatory and antioxidant activities of xanthones from Garcinia mangostana . Abstract : Obesity has reached epidemic proportions worldwide. This condition, and its related diseases such as diabetes and cardiovascular diseases, have become major public health challenges. Fruits are important dietary components, and bioactive constituents from fruits are considered to be a promising source for developing effective and safe anti-obesity drugs. Garcinia mangostana Linn. (Clusiaceae) is a tropical evergreen tree, and its fruit, mangosteen, is called 'Queen of Fruit'. The pericarp of G. mangostana has been used for centuries in Southeast Asia as a medicinal agent for treatment of various diseases. Products derived from mangosteen are widely consumed to ameliorate metabolic dysfunction and resultant metabolic syndrome. However, the chemical principles and mechanisms underlying these effects are unclear. This review summarizes the recent chemical and pharmacological studies related to G. mangostana, including weight reduction, anti-adipogenesis, anti-inflammation and anti-oxidation activity. The aim of this review is to shed light on the role of G. mangostana and its constituents in preventing and treating obesity, which should encourage more interest in the development of relevant therapeutic methods.